The Effect of Work Environment and Work-Life Balance on Employee Retention Mediated by Job Satisfaction - Fatimah Aprilia Wijaya; Lie Liana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of the work environment and work-life balance The effect of job satisfaction on employee retention. The population in this study was 135 employees within the Assistant for Economic and Development Affairs of the Central Java Provincial Secretariat. The data were processed usingsoftwareSPSS version 25. Data analysis techniques include respondent description, variable description, validity test, reliability test, F test, R2 test, and t-test. The results of the study stated that the work environment has a positive and significant effect on job satisfaction, work-life balance has a positive and significant effect on job satisfaction, the work environment has a positive and significant effect on employee retention, work-life balance does not influence employee retention, job satisfaction has a positive and significant influence on employee retention, job satisfaction does not mediate the influence of the work environment on employee retention, and job satisfaction does not mediate the influence work-life balanceon employee retention.